Professionals' perceptions of and recommendations for matching juvenile drug court clients to services. (February 2017) - Korchmaros, Josephine D.; Thompson-Dyck, Kendra; Haring, Rodney C.
Abstract: Current practice in juvenile drug courts is to implement approaches and models that focus on identifying and meeting the needs of the youth through service-matching—such as the Juvenile Drug Court: Strategies In Practice (National Council of Juvenile and Family Court Judges, 2014) and Reclaiming Futures (http://reclaimingfutures.org /), which when combined are JDC/RF programs—to increase effectiveness and produce better outcomes for the youth they serve. This study examined juvenile drug court representatives' reflections on the ability of juvenile drug courts that are implementing JDC/RF programs to match youth with services and the procedures used to do so. Overall, three major cross-JDC/RF site themes related to service-matching emerged from the data: a) Collaboration; b) Engaging Families; and c) Recommendations to Improve Service-Matching. On the whole, JDC/RF staff noted successes in collaborating within the juvenile drug court system and within the community, and in engaging families that facilitated and supported matching youth to services. They also saw opportunities for and noted multiple recommendations, many of which they were in the process of enacting, for continued growth and improvement in the area of matching youth to services. These results suggest that juvenile drug court teams perceived that they can surmount the barriers and challenges of matching youth to services; that adequate and appropriate staffing of juvenile drug courts is critical to effective service-matching; that juvenile drug courts needed to have formalized effective communication systems in place to facilitate and support a system of care focused on service-matching; and that successfully implementing JDC/RF and creating a system that supports service-matching requires juvenile drug courts to balance interagency collaboration and client confidentiality. Highlights: Collaboration is perceived critical to the ability to match youth to services. Families were seen as an important source of information and support for youth. Juvenile drug court teams think they are surmounting challenges of service-matching. Adequate staffing of juvenile drug courts perceived critical to service-matching. Formalized effective communication systems are needed to facilitate service-matching.